Translating Expository Journalistic Texts from Spanish into Arabic: Challenges and Proposals for Didactic Purposes - Al Duweiri, Hussein (Dirasat: Human and Social Sciences, 2021)
Although there are several studies that tackle problems of journalistic translation in various situations, either in English-Arabic or Spanish-Arabic combination, none of these studies sheds light on the stylistic and morphosyntactic problems faced by students of translation. Far from offering a theoretical framework on journalistic translation or analyzing grammatical errors, this study aims at suggesting practical insights on the process of translating expository news texts, specifically, news headlines, lead, information body, punctuation marks, acronyms, abbreviations and proper names. The present study is valuable for both translators-trainers in the teaching and learning of journalistic translation Spanish-Arabic and for anyone interested in this field. It also provides supportive clues and indications for learners of the corresponding languages, since it includes some morphosyntactic and stylistic aspects of journalistic language which are often excluded in language teaching.